Developing Self-Efficacy and Behavioral Intentions Among Underrepresented Students in STEM: The Role of Active Learning - Kuchynka, Sophie; Reifsteck, Tina V.; Gates, Alexander E.; Rivera, Luis M. (Frontiers in Education, 2021)
Two longitudinal studies with students from underrepresented groups investigated the role of active learning interventions in the development of STEM self-efficacy and intentions to pursue STEM in the future. Study 1 longitudinally tracked high school students participating in a four-week geoscience program that applied active learning techniques ranging from hands on experiments to peer discussion. High school student participants displayed increases in self-efficacy and STEM intentions from the start to completion of the program, an effect that was observed exclusively among those who reported strong program quality. Study 2 examined the role of mentorship effectiveness with a sample of community college STEM students interested in transferring to a four-year college. Students’ relatively strong self-efficacy and STEM intentions at the start of the semester remained stable through the end of the semester. Altogether, the present research highlights the role of positive, inclusive educational climates in promoting STEM success among students from underrepresented group members.